2007
DOI: 10.1080/13880200701575098
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential of Various Extracts fromFerula szovitsiana. in Relation to Their Phenolic Content

Abstract: The objective of this study was to examine the in vitro and in vivo antioxidative and radical scavenging potential of organic extracts of the aerial parts and roots of Ferula szovitsiana DC (Umbelliferae). Extracts were evaluated for ferric-reducing antioxidant power (FRAP) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activities in vitro. The influence of the most potent sample was examined in rats for the prevention of plasma and liver lipid peroxidation and activity of antioxidant enzymes cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…2+ , results in formation of a blue color, with a maximum absorbance at 593 nm as described in our previous study [40]. Data was expressed as µM ferric ions reduced to ferrous form per g of tissue.…”
Section: Interaction Of Tptz With Fementioning
confidence: 99%
“…2+ , results in formation of a blue color, with a maximum absorbance at 593 nm as described in our previous study [40]. Data was expressed as µM ferric ions reduced to ferrous form per g of tissue.…”
Section: Interaction Of Tptz With Fementioning
confidence: 99%
“…The interaction of TPTZ with Fe 2+ leads to formation of a blue color, which has a maximum absorbance at 593 nm, as described previously [35]. The data was expressed as µM ferric ions reduced to ferrous form per g of tissue.…”
Section: Ferric Reducing/antioxidant Power (Frap) Assaymentioning
confidence: 99%
“…Hence, the natural antioxidants available in our food source have been suggested as safe for therapy (Athar, 2002). A number of antioxidants have been derived from plants and have been widely studied (Balunas & Kinghorn, 2005;Dehghan et al, 2007;Puvanendran et al, 2008;Rosidah et al, 2008). Numerous studies have also indicated that many plant products, including flavonoids, anthraquinones, tannins, proanthocyanidins, and other phenolics, as well as substances derived from fruit, vegetables, and various plant or herbal extracts, have radicalscavenging activity (Borek, 1997).…”
Section: Introductionmentioning
confidence: 99%